Financial inclusion and inflation in Southeast European countries - Kokorović-Jukan Meldina; Kozarević Emira; Zukić Vesna (Strategic Management)
Background: As a complex socio-economic concept, financial inclusion is related to the improvement of access and use of formal financial products and services (such as bank deposits, loans, insurance, etc.) by all participants in the financial system. More inclusive financial systems contribute to poverty reduction, decrease in inequalities among different income groups leading to economic growth, and economies more resilient towards macroeconomic shocks. Purpose: This paper aims to assess the relationship between financial inclusion and inflation in Southeast European countries, focusing on Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Greece, Montenegro, North Macedonia, Romania, Slovenia, Serbia, and Turkey in the period from 2011 to 2021. Study design/methodology/approach: The financial inclusion index was constructed using Principal Component Analysis (PCA). The connection between the financial inclusion index and inflation was investigated using panel regression modeling (OLS, fixed-effect, and random-effect models). Findings/Conclusions: The research showed that countries with higher levels of financial inclusion are more resilient to inflation. This finding is consistent with other research implying that policymakers and other stakeholders within a financial system should contribute to promoting financial inclusion and building more inclusive financial systems. Limitations/future research: The main limitation of the research is related to data availability for multidimensional index construction. Future research should be directed to providing a better understanding of whether the relationship between financial inclusion and inflation is under the influence of other monetary policy instruments, such as interest rates.